Developmental Toxicity of Mycotoxin Fumonisin B1 in Animal Embryogenesis: An Overview - Lumsangkul, Chompunut; Chiang, Hsin-I; Lo, Neng-Wen; Fan, Yang-Kwang; Ju, Jyh-Cherng (Toxins, 2019)
A teratogenic agent or teratogen can disturb the development of an embryo or a fetus. Fumonisin B1 (FB1), produced by Fusarium verticillioides and F. proliferatum, is among the most commonly seen mycotoxins and contaminants from stale maize and other farm products. It may cause physical or functional defects in embryos or fetuses, if the pregnant animal is exposed to mycotoxin FB1. Due to its high similarity in chemical structure with lipid sphinganine (Sa) and sphingosine (So), the primary component of sphingolipids, FB1 plays a role in competitively inhibiting Sa and So, which are key enzymes in de novo ceramide synthase in the sphingolipid biosynthetic pathway. Therefore, it causes growth retardation and developmental abnormalities to the embryos of hamsters, rats, mice, and chickens. Moreover, maternal FB1 toxicity can be passed onto the embryo or fetus, leading to mortality. FB1 also disrupts folate metabolism via the high-affinity folate transporter that can then result in folate insufficiency. The deficiencies are closely linked to incidences of neural tube defects (NTDs) in mice or humans. The purpose of this review is to understand the toxicity and mechanisms of mycotoxin FB1 on the development of embryos or fetuses.